THOUGHTS OF KH BADAWI HANAFI ON TAUHID EDUCATION IN HIS WORK "THE BOOK OF NIAT INGSUN NGAJI" AND THE IMPLEMENTATION IN STUDENTS OF THE AL IHYA ULUMADDIN ISLAMIC BOARDING SCHOOL, CILACAP - Dian Permana (PROCEEDING AL GHAZALI International Conference, 2023)
In this era of increasing development and ever-dynamic social change, many people have deviated from the teachings of monotheism, thus neglecting the spiritual side, busying themselves too much with the world, because they cannot present God in every aspect of their lives. Humans whose faith is not solid are very, very vulnerable to falling into various kinds of confusion in thinking, doubts, even if they have given up hope, they turn to worldly pleasures such as drugs, corruption, pesugihan, free sex and so on. One alternative to overcome this problem is to apply religious values ​​in everyday life, especialy in the lives of students (Santri). The role of parents is also very necessary to form a good person. The religious values ​​taught to shape a person's behavior and attitudes really depend on how deeply the religious values ​​are embedded in him. The deeper religious values ​​are embedded in a person, the more his religious character and attitudes will be visible and formed automatically. Therefore, it is very important for a Muslim to study and deepen his faith and monotheism. One of them is by studying the book Intentions of Ingsun Ngaji by K.H. Badawi Hanafi Kesugihan. Therefore, it is very important for a Muslim to study and deepen his faith and monotheism. One of them is by studying the book Intentions of Ingsun Ngaji by K.H. Badawi Hanafi, Founder of the Al Ihya Ulumaddin Islamic Boarding School, Kesugihan-Cilacap.